Distribution and molecular characterisation of Lactobacilli in the oral cavity of children - Sonu Singh Ahirwar; Sunil K Snehi; M K Gupta (Wolters Kluwer Medknow Publications, 2021)
Background: Dental caries is a chronic and multifactorial disease mainly caused by microorganisms that are accumulated on soft and hard tissues of oral cavity. Lactobacillus is one of that kind, produces acid after metabolic breakdown of dietary sugar and reduces the pH of oral environment, resulting in teeth demineralisation or dental caries. Aim: The present study focuses on the distribution and characterisation of lactobacilli in the oral cavity of children which are associated with dental caries formation. Methods: Total 116 swab samples were collected from different age groups of children by swabbing the caries surface of teeth. Physiological, morphological and biochemical characteristics of Lactobacillus were analysed. Whole cell protein profiling using SDS-PAGE was also performed for their characterisation. Molecular characterisation of selected isolates was done using 16S-rRNA sequencing for identification. Results: Total 269 isolates were successfully isolated and identified by physiological and biochemical tests according to Bergey's Manual Systematic Bacteriology, which belongs to the seven species of Lactobacillus i.e., L. acidophilus, L. casei, L. delbrueckii, L. helveticus, L. plantarum, L. rhamnosus, L. salivarius. All the isolates were further differentiated by whole cell proteins profiling and species level identification was done by 16S-rRNA gene sequencing method. Conclusions: The present study, suggested that the occurrence of the species of Lactobacillus changes with the age of the individual, but L. rhamnosus (20.54%) and L. acidophilus (18.21%) were abundantly found in age group of 3-12 yr which could be the possible causative agent of dental caries formation in the children of Central India.